Book Review: Experimentelle Archäologie in Europa, Bilanz 2011 - Sina Klausnitz (EXARC, 2013)
Bilanz 2011 once again supplies an exciting, diverse and interesting view into the world of experimental archaeology. Published by EXAR in cooperation with the Pfahlbaumuseum Unteruhldingen, Isensee Verlag, Oldenburg 2011, 270 pp, ISBN 978-3-89995-794-5